Rediseño arquitectónico de mercado de abastos la explanada del cantón Ventanas con el uso de ladrillos artesanales en su envolvente - Macias Roca, Jean Carlos (2023)
The "La Explanada" food market in the Ventanas canton of Los Ríos province plays a crucial role in commerce and the local economy. Although it was established as a solution for informal trade, the market still faces challenges due to the growing presence of informal trade and the lack of adequate infrastructure. To address these issues, a redesign is proposed to ensure safety, hygiene, and comfort for daily business activities. The redesign of "La Explanada" involves a complete restructuring of the existing infrastructure, which includes protection measures against adverse weather conditions and proper management of the waste generated in the market. In addition, it seeks to give the market an aesthetic and functional design that is compatible with the climate of the area, with the aim of improving the user experience and promoting the main economic activity of the location.